Threatened Medicinal Flora of Udanti Wildlife Sanctuary, Chhattisgarh - Patel, Bharati (Indian Forester, 2012)
Udanti Wildlife Sanctuary is an important protected forest area of Chhattisgarh. The sanctuary is densely covered with rich biodiversity. The exploration of this sanctuary yielded 78 medicinally important plant species belonging to 75 genera, under 35 families and. Out of the total 78 plants, 24 species have been accesses to be threatened in India. The habit of the threatened plant species were trees, herbs, shrubs and climbers. Major threats to the medicinal flora of the sanctuary were found to be forest fire and biotic interference.